Potensi Karbon pada Lamun Thalassia hemprichii dan Enhalus acoroides di Perairan Pantai Waai Pulau Ambon - Charlotha Irenny Tupan; Ferdinandus Sangur; Grasiano W Lailossa (Jurnal Sumberdaya Akuatik Indopasifik, 2021)
Seagrass as a high-level plant utilizes carbon dioxide to produce organic matter and stores it in biomass, so that this plant has the potential to reduce carbon dioxide pollution in the environment. This study aimed to analyze the carbon stock and carbon sequestration of two seagrass species in Waai Coastal Waters, Ambon Island. Thalassia hemprichii and Enhalus acoroides were the main focus of this research. These species are the dominant species in Waai Coastal Waters. This research was conducted in June 2019 at two research stations based on substrate differences, namely Station 1 representing a muddy substrate, and Station 2 representing a sandy substrate. The analysis of carbon stocks was carried out using a biomass analysis approach, which was divided into above the substrate and below the substrate. The analysis of carbon sequestration was carried out using the production rate analysis approach. The carbon content analysis was based on the Walkley and Black method. Based on the research results, it was found that the potential carbon stock in E. acoroides ranged from 112.38 - 126.34 gC.m-2. It was higher than T. hemprichii that ranged from 9.31 - 11.28 gC.m-2. This carbon stock was higher at below substrate, especially in the rhizome, which reached 50% of the total carbon stock. The potential of carbon sequestration was also higher in E. acoroides (1.45 - 1.81 gC.m-2.d-1) compared to T. hemprichii (0.43 - 0.54 gC.m-2.d-1). The ability of these two species to absorb and store carbon was better in the muddy substrate area because of the sufficient nutrient content.